1981
DOI: 10.1159/000464212
|View full text |Cite
|
Sign up to set email alerts
|

A New Preparation of Modified Immune Serum Globulin (Human) Suitable for Intravenous Administration

Abstract: The commercial immune serum globulin (ISG) product is suitable for use in passive immunization only by intramuscular administration; intravenous use results in vasomotor side reactions. We report the functional characterization of a chemically modified ISG (MISG) that is essentially free of nonspecific complement-binding activity and contains no new antigenic determinants. The half-life values for MISG given intravenously to rabbits, guinea pigs, and humans are shown not to be different from that of ISG. The M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…We observed that the H2Lz species ('intact' ISG) had been partially reduced and alkylated although at least one of the intraheavy chain disulfide bonds remained unreacted. It is this selective reaction of interheavy chain disulfide bonds which results in the loss of anticomplementary activity, described in Part I1 of this report [9].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…We observed that the H2Lz species ('intact' ISG) had been partially reduced and alkylated although at least one of the intraheavy chain disulfide bonds remained unreacted. It is this selective reaction of interheavy chain disulfide bonds which results in the loss of anticomplementary activity, described in Part I1 of this report [9].…”
Section: Discussionmentioning
confidence: 81%
“…We report here detailed studies on the reaction conditions for reduction and alkylation of ISG, leading to a modified immune serum globulin (MISG) which has a controlled and limited number of reduced and alkylated interchain disulfide bonds. The functional characterization of MISG is reported separately [9].…”
Section: Introductionmentioning
confidence: 99%
“…Chemically modified IVIGs were produced that were structurally intact, were low in anticomplement activity, and contained no IgG fragments. [9][10][11] Treatments of immunoglobulins with enzymes and chemical modification to suppress spontaneous complement activation had several unintended consequences. The treatments also reduced important antibody biological activities required for clinical efficacy.…”
mentioning
confidence: 99%